Fusion beats pacing: Another method of achieving inter- ventricular synchrony. Issue 4 (2019) - Fersia, Omar; Pinheiro, Ricardo; McCarley, Joanne; Pancinha, Cesario; Scullion, John; Cusack, David; Grubb, Neil
No abstract available